From the foundations to the legacy of Minoan archaeology : studies in honour of Professor Keith Branigan - Relaki, Maria; Papadatos, Giannēs, 1972- (Sheffield studies in Aegean archaeology, 2018)
From the Foundations to the Legacy seeks to examine how the developmental trajectory of a single site can offer insights into regional patterns, the importance of integrating local survey information in reconstructing general historical processes and the significance of temporal variability in the construction of space. Evaluating the general frameworks within which Minoan archaeology operates, scholars assess the usefulness of chronological horizons in understanding continuity and change and providing a critical framework for the diachronic analysis of culture, the degree to which the study of settlement patterns can reveal structural continuity through time and the political reach of territorial states. The way the power bases of Minoan society were articulated through the interplay between individual and collective social strategies is the focus of a few papers, further illustrated by in-depth considerations of the role and value of material culture from a social and technological perspective. The largest portion of discussion is devoted to mortuary practices. Some contributors focus on reassessing the significance of micro-patterns in the articulation of mortuary behaviour, while others emphasize broader temporal and spatial processes that affect practices of ostentatious display in burial, all being unified under the overarching perspective provided by recent osteoarchaeological studies which throw critical light on mortuary ritual and the constitution of the social units using the cemeteries. The volume is offered in honour of Keith Branigan's remarkable contribution to the archaeology of Bronze Age Crete and the great inroads his work has made into our understanding of Minoan society. His work has profoundly influenced subsequent generations of archaeologists.